Redução de lead time em projetos: proposta de aplicação da abordagem quick response manufacturing no gerenciamento de projetos que utilizem o PMBOK - Maciel Neto, Jaime Domingues (Universidade Federal de São Carlos, 2012)
Project management is an ancient concept that has been studied since the 1950´s, in the cold war era, when major military projects were developed. Currently this area still has great relevance. This happens because companies can achieve their objectives of short, medium and long term through the implementation of projects. This may occur through exchange of equipment, technological change, expansion or modernization of facilities and development of new products to take advantage of opportunities identified in the market. Thus, it is vital that these projects are well managed, what can be achieved by using as main reference the PMBOK, since this guide is widely known both in the academic and professional environments. Then the time spent on project implementation can be a competitive advantage for the organization, so it is important to reduce the time needed to complete the project. So for this, the concepts and principles of QRM, which is a pragmatic approach aimed at reducing the lead time can be used. This approach is used not only on the shop-floor, but also in the administrative environment. The QRM promotes joint action with the other partners in the supply chain to reduce lead times once it become evident the holistic earned gains. From this context emerges the present work that aims to reduce the lead time in the life cycle of a project, through a proposal to integrate the QRM approach and modern project management given by the PMBOK guide. This proposal will be utilized in an illustrative case study on a project of the oil sector that is sensitive to the term.
Keywords: Administração de projetos; Redução de lead time; Gestão de projetos; Gerenciamento de Projetos; PMBOK; QRM; Project management; Project management body of knowledge; Quick response manufacturing; Lead time reduction; ENGENHARIAS::ENGENHARIA DE PRODUCAO